IPTEKS BAGI MASYARAKAT (IbM) KLASTER INDUSTRI KECIL MAKANAN KHAS DI CANDI MUARO JAMBI - Sri Marmoah; Kasiono Kasiono (Universitas Batanghari Jambi, 2015)
Candi Muaro Jambi sights in Muaro Sebo Muaro Jambi Regency is a tourist attraction that has known both locally as well as nationally. The activities of the community in skim ipteks for society (IbM) aims to identify the typical food of the temple as an icon of Muaro Jambi and is expected to increase the number of tourists visiting the temple as well as a aims to economically empower the society around candi Muaro Jambi. This activity is carried out in five phases, namely: the first orientation and socialization which is held in the village of Jelmu and the village of Muaro Jambi. Both surveys and market potential in the area of candi Muaro Jambi in order of determination of typical temple as towing tourists. The action of the market survey is an activity that is sustainable in tourists travelling in monitor culinary. Results of the third production through training and practice of making fish crackers that were held in the village of Jelmu and the village of Muaro Jambi. Principal activity is the production of action to give birth to the temple area of the culinary icon Muaro Jambi in particular making of